If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 3(v + -13) + -6 Reorder the terms: 18 = 3(-13 + v) + -6 18 = (-13 * 3 + v * 3) + -6 18 = (-39 + 3v) + -6 Reorder the terms: 18 = -39 + -6 + 3v Combine like terms: -39 + -6 = -45 18 = -45 + 3v Solving 18 = -45 + 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. 18 + -3v = -45 + 3v + -3v Combine like terms: 3v + -3v = 0 18 + -3v = -45 + 0 18 + -3v = -45 Add '-18' to each side of the equation. 18 + -18 + -3v = -45 + -18 Combine like terms: 18 + -18 = 0 0 + -3v = -45 + -18 -3v = -45 + -18 Combine like terms: -45 + -18 = -63 -3v = -63 Divide each side by '-3'. v = 21 Simplifying v = 21
| 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h | | 8x-4=y | | 3(x+2)+23= | | 3x+7x-5x= | | 2(y-3)+5=3(x-1) | | 6(-5x+1)=-204 | | 0=1.5x-3.4 | | 2(710+1)= | | 3(-8+8x)=-192 | | (x-2)(x^2-2x+4)-x(x-3)(x+3)=26 | | 5q+-6q-p= | | 1410+2= | | 5(2t+3)=30-5t | | 0=9x^2+12x-3 | | 5x+23=x+3 | | g(5+7)= | | 3x-8=8x+6 | | log(3)0.63= | | 2(14+w)=52 | | =.5x^2-4x+12 | | -2z+3+3+7z=-12 | | 4msquared-24+36=0 | | 6x-23=2x+5 | | -15+48=-3(x+1) | | -x+22=2x+7 | | k+6=-20 | | -8(s+2)=12 | | 58(12+w)= |